Enhancing performance and mitigating overheating in flat plate solar collectors: A UV-selective coating approach-experimental analysis - H Alkhatib (Results in Engineering)
Solar energy has emerged as a highly promising source of renewable energy, with the potential to replace traditional energy sources. Among the key components of solar heating systems is the Flat Plate Solar Collector (FPSC), which captures and converts solar radiation into heat for various applications. However, the efficiency of flat plate solar collectors can be significantly hindered by overheating issues. This study proposes the application of a platinum silver coating to the external side of the glass cover, which selectively blocks ultraviolet waves while allowing 70% of visible light and 70 % of infrared waves to pass through, ultimately resulting in a 38% rejection of solar energy. Experimental and simulation-based efficiency and overheating analyses were conducted using a flat plate solar collector system situated in Dubai, UAE. The results showed an average efficiency reduction of 15% following the application of the coating. Additionally, the stagnation temperature associated with overheating decreased by 19%, from 132.29 °C to 108.7 °C.